Preparation and Characterization of Ir Coating on Mo Network with a W Bond-Coat. Issue 11 (November 2016) - Xin, Wang; Peng, Yan; Jihong, Du; Zhengxian, Li; Yong, Tang; Tao, Yang
Abstract: A bi-layered Ir/W metallic coating was deposited onto the Mo network via a magnetron sputtering method. Results show that the sputtering W bond-coat is able to enhance the binding energy between the sputtering Ir coating and the Mo substrate, and virtually neither delamination nor peeling off is observed for the as-prepared coating. In addition, the interdiffusion between the W bond-coat and the Ir coating or the Mo substrate is not apparent. The dense and adherent Ir coating is identified to have a polycrystalline structure with (111) orientation. According to the three zone model suggested by Movchan and Demchishin for sputtering metallic coatings, the microstructure of the bi-layered metallic coating is consistent with the Zone 1 features. In fact, the bi-layered coating has very low lateral strength and inclines to crack under tension